- #1
- 36
- 1
I’m confused because there are two equations:
1) A=λN
2) A=A0exp^-(λt)
If half-life increases, λ decreases, and A decreases according to 1); but,
If half life increases, λ decreases, hence exp^-(λt) decreases, A should decreases according to 2)
Why is this so? Where went wrong? Thanks!
1) A=λN
2) A=A0exp^-(λt)
If half-life increases, λ decreases, and A decreases according to 1); but,
If half life increases, λ decreases, hence exp^-(λt) decreases, A should decreases according to 2)
Why is this so? Where went wrong? Thanks!